2015
DOI: 10.1108/er-04-2013-0037
|View full text |Cite
|
Sign up to set email alerts
|

The fun paradox

Abstract: Access to this document was granted through an Emerald subscription provided by emeraldsrm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(114 citation statements)
references
References 46 publications
3
77
0
Order By: Relevance
“…Strömberg and Karlsson (2009) refer to these behaviours as organic fun comparing it to organized fun or managed fun, which refers to activities like celebrating personal events and professional milestones, social events, games, competitions and community involvement (Chan 2010;Ford et al 2003a;Karl et al 2005Karl et al , 2008. Plester et al (2015) have identified task related fun, which is fun that employees experience while performing their work tasks.…”
Section: What Is Fun?mentioning
confidence: 99%
See 4 more Smart Citations
“…Strömberg and Karlsson (2009) refer to these behaviours as organic fun comparing it to organized fun or managed fun, which refers to activities like celebrating personal events and professional milestones, social events, games, competitions and community involvement (Chan 2010;Ford et al 2003a;Karl et al 2005Karl et al , 2008. Plester et al (2015) have identified task related fun, which is fun that employees experience while performing their work tasks.…”
Section: What Is Fun?mentioning
confidence: 99%
“…The definitions are limited to presenting a few activities and behaviours, which reflect the problems inherent in trying to find a comprehensive definition, as what is fun is both subjective and context related (Owler et al 2010). In the literature, three main clusters of fun activities and behaviours have already been identified helping researchers to better understand and operationalize the concept of fun; managed (fun activities initiated or supported by the organization), organic (activities that the employees engage in by themselves), and task related, but, little has been done so far to clearly distinguish among them (Plester et al 2015). Adding to the above, we know little regarding the interconnections among the three categories of fun activities and behaviours; for example how is managed fun related to organic fun, or is there a difference between fun activities organized by the employees themselves and fun activities organized by the management, resulting in a fourth category, that we can call organized fun and differentiate it from managed fun?…”
Section: What Is Fun?mentioning
confidence: 99%
See 3 more Smart Citations